Internet Use Effects on Loneliness Through Self-Objectification Among Junior High School Students - Kamila, Bina Aulia; Mulyono, Yatin; Pamungkas, Ari (Research Horizon, 2025)
The rapid rise of digital technology has increased problematic internet use among adolescents, raising concerns about its impact on loneliness, particularly in non-Western contexts like Indonesia. This study aimed to examine whether self-objectification mediates the relationship between problematic internet use and loneliness among Indonesian junior high school students. A quantitative correlational design was employed, involving 357 students aged 13–15 years from five diverse schools in Central Kalimantan, selected via proportionate stratified random sampling. Data were collected using standardized questionnaires and analyzed with PROCESS Macro Hayes Model 4 with 5,000 bootstrap samples. Findings revealed a significant direct effect of problematic internet use on loneliness, but no significant relationships between problematic internet use and self-objectification or self-objectification and loneliness. The mediation effect of self-objectification was also non-significant. These results suggest that problematic internet use directly contributes to loneliness without self-objectification as a mediator, highlighting the need for digital wellness programs to promote balanced internet use and foster offline social connections among Indonesian adolescents.